Impact of microbial iron oxide reduction on the transport of diffusible tracers and non-diffusible nanoparticles in soils. (April 2019) - Liang, Xiaolong; Radosevich, Mark; Löffler, Frank; Schaeffer, Sean M.; Zhuang, Jie
Abstract: In subsurface bioremediation, electron donor addition promotes microbial Fe(III)-oxide mineral reduction that could change soil pore structure, release colloids, and alter soil surface properties. These processes in turn may impact bioremediation rates and the ultimate fate of contaminants. Columns packed with water-stable, Fe-oxide-rich soil aggregates were infused with acetate-containing artificial groundwater and operated for 20 d or 60 d inside an anoxic chamber. Soluble Fe(II) and soil colloids were detected in the effluent within one week after initiation of the acetate addition, demonstrating Fe(III)-bioreduction and colloid formation. Diffusible Br −, less diffusible 2, 6-difluorobenzoate (DFBA), and non-diffusible silica-shelled silver nanoparticles (SSSNP) were used as tracers in transport experiments before and after the bioreduction. The transport of Br − was not influenced by the bioreduction. DFBA showed earlier breakthrough and less tailing after the bioreduction, suggesting alterations in flow paths and soil surface chemistry during the 20-d bioreduction treatment. Similarly, the bioreduction increased the transport of SSSNP very significantly, with mass recovery increasing from 1.7% to 25.1%. Unexpectedly, the SSSNP was completely retained in the columns when the acetate injection was extended from 20 to 60 d, while the mass recovery of DFBA decreased from 89.1% to 84.1% and Br − showed no change. The large change in the transport of SSSNP was attributed to soil aggregate breakdown and colloid release (causing mechanical straining of SSSNP) and the exposure of iron oxide surfaces previously unavailable within aggregate interiors (facilitating attachment of SSSNP). These results suggest a time-dependent fashion of microbial effect on the transport of diffusivity-varying tracers. Graphical abstract: Image 1 Highlights: Fe(III)-bioreduction causes time-dependent aggregate breakdown and colloid release. Short-term bioreduction alters soil surface chemistry and solute/nanoparticle transport. Electron donor amendment enhances transport of nanoparticles.